(untitled) (Medico Legal Update, 2020)
This article deals with the psychological assessment of equivocal death. As an investigator it is important to possess the knowledge of the cause and manner of the circumstances surrounding any suspicious death. The authors of this study have explored in detail the procedures involved in the equivocal death investigations and protocols followed during the conduct of the interview by the investigators. However, the psychological autopsy report has certain guidelines to be prepared and needs to be evaluated in-depth before any conclusions is to be drawn. To be politically correct, this paper will leave no stone unturned in terms of psychological assessment of the deceased role in the death.